Physiological and transcriptional responses of seed germination to moderate drought in Apocynum venetum - Wu, Zhibo; Chang, Peixiu; Zhao, Jing; Li, Di; Wang, Wenshu; Cui, Xiuwen; Li, Mengfei (Frontiers in Ecology and Evolution, 2022)
Apocynum venetum L. is an endangered perennial species mainly distributed in the semi-arid lands and plays an important role in protecting ecological environment; meanwhile, it is also widely used as a traditional Chinese medicine. While physiological changes of seed germination under drought stress have been conducted, the adaptive mechanism to semi-arid environment is still unknown. Here, the physiological and transcriptional changes during seed germination of A. venetum under different PEG-6000 treatments (5% to 20%) were examined. The germination characteristics (germination rate, radicle length and fresh weight) were promoted under moderate drought (5% PEG). The activities of antioxidant enzymes (SOD and POD) and contents of osmolytes (soluble sugar, MDA and Pro) were increased while the CAT and APX activities and the protein content decreased with the increase of PEG concentrations. A total of 2159 (1846 UR, 313 DR) and 1530 (1038 UR, 492 DR) DEGs were observed during seed germination at 5% and 25% PEG vs. CK, respectively; and 834 co-expressed DEGs were classified into 10 categories including stress response (67), primary metabolism (189), photosynthesis and energy (83), cell morphogenesis (62), secondary metabolism (21), transport (93), TF (24), transcription (42), translation (159) and bio-signaling (94). The RELs of representative genes directly associated with drought stress and seed germination were coherent with the changes of antioxidant enzymes activities and osmolytes contents. These findings will provide useful information for revealing adaptive mechanism of A. venetum to semi-arid environment.